Existence of Viscosity Solutions to a System of Hyperbolic Balance Laws (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the existence of viscous solutions of a hyperbolicequilibrium law system derived from the nonlinear entropy moment closure ofa dynamic equation is established. In addition, by using the natural entropyof the system, some higher order estimates of some viscosity solutions areobtained.